Analysis of Space-Flight Radiation Damage to ExoMars Trace Gas Orbiter NOMAD-UVIS Spectrometer - Ramdeo, James (Cranfield University, 2025)
​​ExoMars Trace Gas Orbiter (TGO) mission, launched in 2016 as part of the European Space Agency (ESA) ExoMars programme, carries the Nadir and Occultation for MArs Discovery (NOMAD) instrument suite which consists of the Ultraviolet and Visible Spectrometer (UVIS). Operating in Martian orbit, NOMAD-UVIS is subject to accumulating radiation-induced degradation that can impact detector performance and long-term data quality. This study explores radiation-induced damage to NOMAD-UVIS through an analysis of dark current evolution, integrating both pre-flight ground testing data and in-flight mission data. The results establish a comparison between ground test predictions of radiation-induced dark current via the use of estimated radiation doses, and the actual in-flight performance of the detector with consideration of the Martian radiation environment.​
Dryer, Ben – Associate Supervisor – Open University Mason, Jon – Associate Supervisor – Open University
Keywords: CCD; Dark Current; Annealing; Dark Frames; Spectrometer; Bright Pixels